Zircon as a tracer of plumbing processes in an active magmatic system: insights from mingled magmas of the 2010 dome collapse, Montserrat, Lesser Antilles Arc, Caribbean - Scarrow, Jane H.; Schmitt, Axel Karl; Barclay, Jenni; Horstwood, Matthew; Bloore, Andrew J.; Christopher, Thomas E. (Journal of volcanology and geothermal research, 2021)
Soufrière Hills Volcano, Montserrat, erupted from 1995 to 2010, with activity including dome growth, destructive pyroclastic density currents and Vulcanian explosions. Monitoring data, such as gas emissions, show the system is still in a state of unrest. The recent eruptions provide an opportunity to study, in real time, a complex subduction-related subvolcanic transcrustal melt-mush reservoir, its magma fluxes, and the timing of crystal and melt storage prior to eruptive paroxysms. How and when mush destabilisation occurs prior to volcanic eruptions continues to be a question of intense debate. Evidence of mafic magma intrusion, a potential eruptive trigger, is preserved in enclaves with quenched and diffuse margins that are mingled with crystal-rich andesite. Here, in this first study of Soufrière Hills Volcano zircon, we report zircon ages and compositions for mafic-intermediate enclaves and host andesites from the most recent dome collapse in 2010 to place temporal constraints on magma reservoir processes. Zircon 238U-230Th disequilibrium crystallisation ages ranging between c. 2-250 ka constrain the longevity of the magmatic plumbing system. Uniform Hf isotopes, εHf 11.3 ± 1.2 to 14.6 ± 1.5, indicate invariant compositions that are typical for island arc magma sources. Zircon trace element concentrations and Ti-in-zircon crystallisation temperatures indicate crystallisation in isolated, small-volume, lenses with variable fractions of melt of heterogeneous compositions. We suggest amalgamation of assorted crystal cargoes from these lenses occurred prior to eruption during mush destabilisation triggered by mafic magma recharge. Zircon textures, on the other hand, shed light on recent centimetre-scale magma mingling immediately prior to eruption. Euhedral-subhedral zircon is preferentially preserved in or near quenched contacts of the least-evolved enclave and host andesite. By contrast, reheating of the andesite by the mafic magma recharge in the presence of zircon-undersaturated melts promoted zircon resorption. This led to the formation of subhedral-anhedral corroded zircon that is typical in the host andesite mush. Zircon thus reveals processes ranging from 100,000s of years of andesite storage to short-term partial destruction in response to transient heating and magma mixing events.